2020
DOI: 10.1029/2020jc016243
|View full text |Cite
|
Sign up to set email alerts
|

Composite of Typhoon‐Induced Sea Surface Temperature and Chlorophyll‐a Responses in the South China Sea

Abstract: Sixteen years of data on typhoons in the South China Sea (SCS) are used to investigate their impacts on sea surface temperature (SST) and chlorophyll-a (Chl-a). The time series of SST and Chl-a before and after typhoons are composited for all typhoon locations to assess their responses. Decreases in SST and increases in Chl-a occur after 73% and 70% of the typhoons, respectively, with overall averaged changes equal to −0.42 ± 0.015°C and 0.056 ± 0.003 log 10 mg/m 3 , respectively. The largest responses are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 64 publications
1
53
1
1
Order By: Relevance
“…The decrease in SST is a well-known phenomenon associated with typhoons; in comparison, the typhoon-induced variation in chlorophyll concentration is much more complex and varies by case. Increased chlorophyll concentrations are found in 70 % of typhoons in the South China Sea (Wang, 2020) and 18 % of typhoons in the northwest Pacific Ocean (Lin, 2012). These satellite-derived observations of increased surface chlorophyll may be due to enhanced nutrient flux into surface waters from either vertical mixing or enhanced upwelling reaching beyond the nutricline (Zhang et al, 2018), or as shown here, simply mixing of phytoplankton biomass in the DCM throughout the mixed layer (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The decrease in SST is a well-known phenomenon associated with typhoons; in comparison, the typhoon-induced variation in chlorophyll concentration is much more complex and varies by case. Increased chlorophyll concentrations are found in 70 % of typhoons in the South China Sea (Wang, 2020) and 18 % of typhoons in the northwest Pacific Ocean (Lin, 2012). These satellite-derived observations of increased surface chlorophyll may be due to enhanced nutrient flux into surface waters from either vertical mixing or enhanced upwelling reaching beyond the nutricline (Zhang et al, 2018), or as shown here, simply mixing of phytoplankton biomass in the DCM throughout the mixed layer (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…4a and b). Additionally, the wind stress increased before the arrival of the typhoon, resulting in ahead-of-eye cooling and mixing that has been shown to take place a few days earlier (Glenn et al, 2016;Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…TC-induced breaking and unbreaking surface waves also contribute to turbulence in the upper ocean and deepening of the mixed layer (He and Chen, 2011;Toffoli et al 2012;Aijaz et al 2017;Stoney et al 2017;Zhang et al 2018a, b). The wave-breaking-induced acceleration transfers momentum from surface waves to surface currents and also contributes to sediment transport 2020). Non-breaking surface wave-induced mixing in numerical model improves the simulations of sea surface temperature and TC track (Guan and Zhao 2014;Li et al 2014;Aijaz et al 2017;Stoney et al 2017).…”
Section: Figmentioning
confidence: 94%
“…TC-induced mixing, enhanced terrestrial runoff and resuspension are considered three major processes that contribute to the increased nutrient concentrations and subsequent primary production in the euphotic layer (Chen et al 2003). The chlorophyll-a reaches its peak three days after nitrate peak after a TC (Pan et al 2017), and TC-induced phytoplankton blooms usually last for two to three weeks (Babin et al 2004;Chen and Tang 2012;Foltz et al 2015;Wang 2020).…”
Section: Biological Responsementioning
confidence: 99%
“…The concentration of Chl-a in the coastal sea surface of the Beibu Gulf in Guangxi exhibited strong seasonal changes, with the following ranking being apparent: summer > autumn > spring and winter (Figure 12). The Chl-a concentration in summer and autumn was mainly affected by the climate [49,50]. In summer, the Beibu Gulf receives abundant rainfall.…”
Section: Temporal Variation Of Chl-amentioning
confidence: 99%